$\newcommand{\cov}{\operatorname{cov}}$I want to find the covariance between the sample mean and the sample variance, I think I am along the right track but am not sure.

Suppose we have i.i.d. random variables $X_1, X_2, \ldots, X_n$.


$$\overline{X} = \frac{1}{n} \sum_{i=1}^n X_i \text{ and } S^2 = \frac{1}{2n(n-1)} \sum_{i=1}^n \sum_{j=1}^n (X_i - X_j)^2 $$

I want to find their covariance $\cov(\overline{X}, S^2)$. Here is what I have done:

\begin{align} & \cov(\overline{X}, S^2) = \cov\left(\frac{1}{n}\sum_{i=1}^n X_i, \frac{1}{2n(n-1)} \sum_{i=1}^n\sum_{j=1}^n (X_i - X_j)^2 \right) \\ = {} & \frac{1}{2n^2(n-1)} \sum_{i=1}^n \cov(X_i,\sum_{k=1}^{n}\sum_{j=1}^{n} (X_k - X_j)^2) \\ = {} & \frac{1}{2n^2(n-1)} \sum_{i=1}^n \cov(X_i,2\sum_{k=1}^{n} (X_i - X_k)^2) \end{align}

(because $\cov(X_i, (X_a - X_b)^2)$ is zero if $i$ isn't $a$ or $b$)

$$= \frac{1}{n^2(n-1)} \sum_{i=1}^{n} \sum_{k=1}^n \cov(X_i, (X_i - X_k)^2).$$

Now, I compute $\cov(X_i, (X_i - X_k)^2)$:

for $ i = k, \cov(X_i, (X_i - X_k)^2) = 0$

for $ i \neq k,$

\begin{align} & \cov(X_i, (X_i - X_k)^2) = \cov(X_i, X_i^2 - 2X_iX_k + X_k^2) = \cov(X_i, X_i^2) - 2\cov(X_i, X_iX_k) \\[8pt] = {} & E(X^3) - E(X)E(X^2) -2E(X)E(X^2) + 2(E(X))^3 \\[8pt] = {} & E(X^3) -3E(X)E(X^2) + 2(E(X))^3. \end{align}

When I plug this in, I do not get the answer that I want which is $E(X-E(X))^3$, can anyone please tell me where I went wrong?

UPDATE: I plugged it in again and it is actually correct! Sorry for being so careless. Thanks to anyone who has read the question. Should I delete this post?

  • $\begingroup$ Does $\operatorname E(X-\operatorname E(X))^3$ mean $(\operatorname E(X-\operatorname E(X)))^3$ or $\operatorname E((X-\operatorname E(X))^3) \text{ ?}$ I would guess the latter, but I prefer being explicit about this. $\endgroup$ – Michael Hardy Jul 10 '18 at 17:27
  • 2
    $\begingroup$ In more conventional notation, $S^2$ often denotes $\displaystyle \frac 1 {n-1} \sum_{i=1}^n \big( X_i -\overline X \,\big)^2.$ I haven't checked whether your notation agrees with that, but can you tell us whether you intended it to be the same thing? $\qquad$ $\endgroup$ – Michael Hardy Jul 10 '18 at 17:31
  • $\begingroup$ $E(X - E(X))^3$ means $E((X - E(X))^3)$. $\endgroup$ – Noppawee Apichonpongpan Jul 11 '18 at 3:08
  • 1
    $\begingroup$ Yes, my book also uses $S^2 = \frac{1}{n-1} \sum_{i=1}^{n} (X_i - \overline X)^2$, but the first part of the exercise is actually to show that $S^2 = \frac{1}{2n(n-1)} \sum_{i=1}^{n} \sum_{j=1}^{n} (X_i - X_j)^2$, so they are equal. $\endgroup$ – Noppawee Apichonpongpan Jul 11 '18 at 3:10
  • 1
    $\begingroup$ Since they are equal, why not use the simpler form? $\endgroup$ – Michael Hardy Jul 11 '18 at 6:36

I hope this will help you to find a mistake.


  • $\begingroup$ It's behind a pay wall...? $\endgroup$ – Noppawee Apichonpongpan Jul 10 '18 at 14:29
  • $\begingroup$ I suggest you to check the result for $Cov(X_{i},X_{i}X_{k})$. $\endgroup$ – Mr.M Jul 10 '18 at 14:38
  • $\begingroup$ $Cov(X_i, X_i X_k) = E(X_i^2 X_k) - E(X_i)E(X_i X_k) = E(X_i^2)E(X_k) - (E(X_i))^2E(X_k) = E(X^2)E(X) - (E(X))^3$ $\endgroup$ – Noppawee Apichonpongpan Jul 10 '18 at 14:54
  • $\begingroup$ Is that not correct? $\endgroup$ – Noppawee Apichonpongpan Jul 10 '18 at 14:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.